Effect of five staining solutions on the colour stability of two acrylics and three composite resins based provisional restorations - (:unkn) unknown (My University, 2006)
The effect of coffee, tea, coca-cola, orange-juice and red wine on the colour stability of acrylic and composite based provisional materials were evaluated. Two acrylic resins and three composite resins were studied. 48 standardized specimens for each provisional material were prepared. Each group was divided into 6 subgroups. Specimens from each group were immersed in staining solutions at room temperature for 30 days. Red wine and tea caused the most significant colour changes and orange juice showed the least significant colour changes. deltaE of all of the provisional restorations materials was changed after the immersion in all of the staining solutions during the experimental process.
Keywords: Materials Testing; Analysis of Variance; Dental Materials; Acrylic Resins; Composite Resins; Tea; Denture, Partial, Temporary; Color; Beverages; Dental Restoration, Temporary; Citrus sinensis; Coffee; Cola; Wine; Colorimetry; Prosthesis Coloring